TINJAUAN YURIDIS IMPLEMENTASI PRINSIP SYARIAH PADA PEMBIAYAAN HUNIAN SYARIAH (PHS) KONGSI DENGAN AKAD MUSYARAKAH MUTANAQISAH DI PT. BANK MUAMALAT INDONESIA Tbk CABANG KALIMALANG KOTA - ASTUTI, BENI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This study is aimed at understanding and analyzing the consideration for the issuance of the product of syariah residential financing (PHS) partnership and the implementation of syariah principles to the product of syariah residential financing under Musyarakah Mutanaqisah agreement at PT. Bank Muamalat Indonesia, Tbk., Kalimalang Kota Bekasi Branch. This is a judicial-normative study, which tries to look into a procedure of finding the truth based on legal scientific logics from its normative points of view conducted by means of bibliographical study and reviewing relevant legal principles (laws and regulations) and its legal principles. To compete the collected data, in addition to bibliographical study, some field study was also conducted. This research is presented in a analytical-descriptive-report in which the processed data was then quantitatively analyzed. The results of the study show that (1) the consideration for the issuance of the product of syariah residential financing (PHS) in partnership with Musyarakah Mutanaqisah agreement at PT. Bank Muamalat Indonesia, Tbk., Kalimalang Kota Bekasi Branch, which was referred to in the imutes of meeting of the syariah supervisory board (DPS), which is regarded as not in conflict with of against the fatwas or rulings issued by the national Syariah Board (DSN), which, among others, are as follows: (a) Syariah Residential Financing (PHS) in partnership with Musyarakah Mutanaqisah and Ijarah Agreement was aimed at socializing the financing based on syariah principles, (b) Bank Muamalat adopts basic concepts which are known in other countries, that is, the use of house ownership agreement under syariah principles using musyarakah mutanaqisah agreement which constitutes the combination of musyarakah and ijarah agreement as one operational system of syariah house ownership financing, (2) the implementation of syariah principles on the product of Syariah Residential Financing (PHS) Partnership has been in conformity with relevant laws and fatwas or rulings.